Letter: Baseline age on antiviral treatment may significantly influence the clinical response of children with chronic hepatitis B - Li, Jing; Wu, Yaxin; Wang, Fu‐Sheng (Alimentary pharmacology & therapeutics, 2024)
LINKED CONTENT This article is linked to Wu et al papers. To view these articles, visit https://doi.org/10.1111/apt.17667 and https://doi.org/10.1111/apt.17843